EXPERIENCE OF USING THE INSTITUTION OF PLEA BARGAIN AGREEMENT IN THE LEGISLATION OF THE USA - Otabek Toshev (Galaxy International Interdisciplinary Research Journal, 2022)
In this article the author provided the peculiarities of the institution of plea bargaining, by comparative analyse of the experience of the USA and Russian countries, studied the different aspects of this institution from other institutions, the main positive aspects of the legislation of foreign countries on the the institution of plea bargaining, the difference between concepts of plea guilty and plea bargain agreement, the procedure for appealing a judgment rendered by the institution, significant aspects of the plea bargaining procedure and also the positive and negative sides of the institute. The role of the court in concluding a plea agreement, the defendant's rights in the proceedings, the differences between the "plea bargain agreement", the "cooperation agreement" and the "agreement on the application of abbreviated forms of litigation" and their essence are described. As well as, proposals were put forward to improve the institution of plea bargaining, that is, to introduce a petition for participation in the legislation of the victim in the conclusion of an agreement, to strengthen the right to participate in the judicial complex, to enter into an agreement on confession on charges, from the moment of obtaining the status of the defendant.